El ganado vacuno en Sumer y Acad - Delgado Linacero, Cristina (Espacio Tiempo y Forma. Serie II, Historia Antigua, 1996)
Cattle were a very important domesticated species in the Near East with goats and sheep. They hoid a special and central place in economy of agro-pastoral ancient society in Mesopotamia, providing good resources of meat, dairy producís, leather and dung, besides labor and draft. However, the highest cost of cattie breeding resulted in a poor diet from these peoples and led to the almost exclusive possession of these animáis by the ruling classes. The valuable and commercial characteristic of cattie was transferred to the religious sphere where its offering and sacrifico became the best gift for the divinity. The sacrificial feasts turned out to be, in many cases, an excellent occasion for the consumption of a special dish which only few people could normally enjoy everyday life.